2019 WSGC Intercollegiate Rocket Engineering Competition - Tollison, Chandler R; Guither, Adrian; DeVries, Christina; Dickler, Jane; taylor, Ethan (Proceedings of the Wisconsin Space Conference, 2020)
The Intercollegiate Rocket Engineering Competition is held by the Experimental Sounding Rocket Association every year at Spaceport America, New Mexico. The competition has many categories, and Pioneer Rocketry chose to compete in the 10k COTS category, flying Something Cheesy to an altitude of 10,000 feet on a commercial motor, with a 4 Kg payload. The payload studied the breakdown voltage of air with respect to altitude. Pioneer Rocketry is proud to report that Something Cheesy had a safe and successful flight and recovery. Unfortunately, due to a motor anomaly, Something Cheesy flew short of its 10,000-foot goal. The team is proud to have represented the state of Wisconsin at this international event, winning the “Cheesiest Rocket” award, as well as being runner up for the spirit award.